1976
DOI: 10.1007/bf01175118
|View full text |Cite
|
Sign up to set email alerts
|

Morphogenesis of rat muscle spindles after nerve lesion during early postnatal development

Abstract: The influence of innervation on muscle spindle morphogenesis has been investigated in rat hind-limb muscles by sectioning the sciatic nerve, with suture of the stumps, at various postnatal stages. After nerve section at 4 or 7 days of age a proportion of spindles survived during the denervation phase and developed, during the subsequent reinnervation phase, into atypical structures. The reinnervated spindles were recognized by the presence of a limiting capsule but lacked the characteristic distinction of equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Schiaffino and Pierobon Bormioli (1976) have shown that, following denervation of muscle in neonatal rats, all the intrafusal fibers lack sensory terminals, although the reinnervating axons reach near or within the capsules. It is possible that the formation and subsequent differentiation of spindles may rely on different mechanisms: The former may be induced by the arrival of sensory fibers at the region abutting the target site, whereas the latter may require the formation of sensory terminals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schiaffino and Pierobon Bormioli (1976) have shown that, following denervation of muscle in neonatal rats, all the intrafusal fibers lack sensory terminals, although the reinnervating axons reach near or within the capsules. It is possible that the formation and subsequent differentiation of spindles may rely on different mechanisms: The former may be induced by the arrival of sensory fibers at the region abutting the target site, whereas the latter may require the formation of sensory terminals.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 7 shows the distribution of diameters of intrafusal fibers measured at the equatorial region. On the nerve-crushed side, many intrafusal fibers showed no clear nuclear profile that distinguished between the nuclear bag and chain types (Schiaffino and Pierobon Bormioli, 1976;Werner, 1973b), although the 2 types could be identified in some spindles (Fig. 5).…”
Section: Alterations Of Intrafusalfibersmentioning
confidence: 99%
“…Accordingly, sensory but not motor denervation in developing muscle prevents the appearance of slow tonic myosin in the intrafusal fibers (444). Sensory neurons are also responsible for blocking the growth of intrafusal fibers: these undergo marked hypertrophy resembling extrafusal fibers after nerve lesion in 4-to 7-day-old rats, which causes disappearance of sensory nerve terminals in most spindles, typical thin intrafusal fibers being only found in the rare spindles with sensory terminals (712). It has been suggested that intrafusal fibers are maintained in an immature state by sensory innervation, both with respect to growth and MyHC complement (843).…”
Section: Differentiation Of Intrafusal Fibers In Muscle Spindlesmentioning
confidence: 99%
“…The critical period during which rat muscle spindles undergo degeneration after denervation extends over the first 8-10 postnatal days (Werner 1973). Fewer muscle spindles and intrafusal fibres disintegrate when muscles are denervated several days after birth (Werner 1973;Schiaffino and Pierobon-Bormioli 1976). From the 14th postnatal day onwards, most muscle spindles survive denervation and are reinnervated after nerve regeneration (Zelen4 and HnN 1963;Schrtider 1974a, b;Schiafflno and Pierobon-Bormioli 1976).…”
Section: Introductionmentioning
confidence: 99%